DETERMINANTS OF PERFORMANCE OF DEVELOPMENT UNIVERSITAS PEMBANGUNAN PANCA BUDI MEDAN - Firmansyah, Firmansyah; Farida Ferine, Kiki; Nizamuddin, Nizamuddin (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The purpose of this research is to determine and analyze the use of information technology and organizational culture on employee performance with competency as an intervening variable. The type of research carried out was associative quantitative, the research was carried out at the Panca Budi Development University, Medan. The research population was 153 employees, and the research population was all sampled and the sampling technique was a census sample. The research model used is Pahat analysis and research calculation tools using Smart PLS 3.3.3. The data collection techniques used were questionnaires and surveys. Based on the results of research that has been carried out and data analysis as explained in the previous chapter, the following conclusions from the research results are presented as follows: Information Technology has a positive and significant effect on Competency. Organizational culture has a positive and insignificant effect on competence. Information Technology has a positive and significant effect on Employee Performance. Organizational culture has a positive and insignificant effect on employee performance. Competency has an insignificant positive effect on employee performance. Information Technology has a positive and insignificant effect on Employee Performance through Competency. Organizational culture has a positive and insignificant effect on employee performance through competency.